Antiangiogenic therapy of head and neck squamous cell carcinoma by vascular endothelial growth factor antisense therapy - Riedel, Frank; Götte, Karl; Hörmann, Karl; Grandis, Jennifer R. (Current research in head and neck cancer, 2005)
Angiogenesis is increased in various human cancers, including head and neck squamous cell carcinoma (HNSCC), and correlates with tumor progression and metastasis. Vascular endothelial growth factor (VEGF) has been shown to be a key regulator of angiogenesis. We determined whether VEGF antisense oligonucleotide treatment can decrease the angiogenic activity of HNSCC cell lines in vitro and of HNSCC xenografts in vivo. Established human HNSCC cell lines were screened for VEGF expression at both mRNA and protein levels. By using a 21-mer antisense phosphorothioate oligonucleotide targeting the translation start site of human VEGF mRNA, we examined the modulation of VEGF expression in cell line supernatants by capture ELISA and in cell lysates by Western blotting. Human endothelial cells were grown in conditioned medium produced from the treated tumor cells. Endothelial cell proliferation was determined by cell count, and endothelial cell migration was measured using a modified Boyden chamber. Mice with HNSCC xenografts were treated with PBS, VEGF antisense or sense oligonucleotides (10 mg/kg i.p. injection, 3 times/week), respectively, and tumor volumes were measured for 5 weeks. VEGF antisense oligonucleotide treatment resulted in a significant reduction of VEGF protein expression compared to treatment with the sense control. Although the growth rate of the tumor cell lines was not affected, the addition of conditioned medium from VEGF antisense-treated tumor cells resulted in decreased endothelial cell proliferation and migration. VEGF antisense oligonucleotide treatment of HNSCC xenografts resulted in a significant tumor growth suppression. These results suggest that downmodulation of VEGF using antisense oligonucleotides may be a potential therapy for the inhibition of angiogenesis in HNSCC.
Gesehen am 01.04.2022